Surgical excision of Infantile Haemangiomas: a technical refinement to prevent bleeding complications - F. Leone; E. Benanti; A. Marchesi; S. Marcelli; R. Gazzola; L. Vaienti (PAGEPress Publications, 2014)
Purpose: The aim of the study is to improve operative speed and precision of haemangiomas excision. Methods: Case-report: haemangioma is a common affection of the 8% of the population during the neonatal period. In complicated cases and involution sequelae surgical treatment is the first choice. The Authors propose a surgical refinement to prevent intraoperative bleeding. Methods: several suture stitches were placed around the hemangioma. The edges of the lesion became more defined, thus allowing accurate excision. Results and Conclusions: Haemangiomas are characterized by rich blood supply. Surgery is often hindered by massive bleeding and Temporary placement of full-thickness sutures, surrounding the hemangioma, allowed a noticeable improvement in hemostasis precision and greater definition of the margins of the hemangioma.